1997
DOI: 10.1055/s-0038-1655950
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Five Rapid D-Dimer Assays Compared to ELISA in the Exclusion of Deep Venous Thrombosis

Abstract: SummaryStudies measuring the fibrin degradation product D-Dimer (DD) using enzyme-linked immunosorbent assays (ELISA) in patients with venographically proven deep venous thrombosis (DVT) suggest that it is possible to exclude DVT when DD level is below a certain cut-off level. However, ELISA methods are time-consuming and not available in all laboratories. Different rapid latex-agglutination assays have been investigated, but their sensitivity is considerably lower.In the present study we compared the value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 25 publications
5
93
0
4
Order By: Relevance
“…We believe the diagnosis of UAP at admission to the ED should be based on clinical factors such as history, physical examination, and electrocardiography, and not on blood markers. Moreover, the generally low specificity of the available D-dimer assays (ELISA, latex agglutination assay, turbidometric immunoassays) and their wide variations in sensitivity [16][17][18] preclude their use as a diagnostic tool [16,[19][20][21][22]. Because of the low interassay correlation [21,22] and the lack of a D-dimer reference standard, we used the ELISA, which is currently considered the gold-standard methodology.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the diagnosis of UAP at admission to the ED should be based on clinical factors such as history, physical examination, and electrocardiography, and not on blood markers. Moreover, the generally low specificity of the available D-dimer assays (ELISA, latex agglutination assay, turbidometric immunoassays) and their wide variations in sensitivity [16][17][18] preclude their use as a diagnostic tool [16,[19][20][21][22]. Because of the low interassay correlation [21,22] and the lack of a D-dimer reference standard, we used the ELISA, which is currently considered the gold-standard methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Our review found results for the quantitative assays frequently reported at different cut points. In several studies the cut point was not determined a priori but instead was chosen retrospectively to maximize the sensitivity of the assay (19,(25)(26)(27).…”
Section: Differences Among D-dimer Assaysmentioning
confidence: 99%
“…D-dimers were measured with a widely used quantitative latex assay (Tinaquant; Roche GmbH), which reaches a sensitivity for detection of thromboembolic disease of Ͼ95%, with a cutoff value of 500 g/L. 14 …”
Section: D-dimer Analysismentioning
confidence: 99%
“…12,13 Techniques for the quantitative detection of circulating D-dimers have improved such that the assay is now inexpensive and readily available. 12,14 The aim of this study was to determine whether D-dimer measurement would be sensitive enough to reliably detect thrombosis in cerebral sinuses, a condition in which the clot volume is often considerably smaller than it is in extracranial venous thromboembolic disease.…”
mentioning
confidence: 99%